Advances in neuropharmacology : drugs and therapeutics - Sahab Uddin, Md., 1992-; Rashid, Mamunur (Professor of pharmacology) (Oakville, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
"This new volume, Advances in Neuropharmacology: Drugs and Therapeutics, provides a comprehensive overview of the drugs that act on the central and peripheral nervous systems. It thoroughly describes the diseases that are associated with the nervous system and drugs used their treatment while also looking at the current status of these drugs and their future potential and challenges. This book is divided into three sections that describe the nervous system associated diseases and their treatment as well as current status and future opportunities and challenges. Section 1 focuses on the drugs that affect the functions of the autonomic nervous system to produce therapeutic effects. These drugs may act presynaptically by manipulating the genesis, storage, and secretion, and by blocking the action of neurotransmitters. Some drugs may trigger or impede postsynaptic receptors. Section 2 focuses on drugs that affect the central nervous system, including antianxiety drugs, sedative and hypnotic drugs, antidepressant drugs, antipsychotic drugs, antiepileptic drugs, and many more. It covers the pharmacological management of various diseases, including Alzheimer's, Parkinson's, Huntington's disease, and others. Section 3 offers explanations of neurochemical interactions with the aim to develop drugs that have beneficial effects on neurochemical imbalances. This section demonstrates models to assess the transport of drugs across the blood-brain barrier and nanomedicine to treat brain disorders. This rich compilation provides thorough and extensive research updates on the important advances in neuropharmacological drugs and drug therapy from experienced and eminent academicians, researchers, and scientists from throughout the world. It will be rich resource for professionals, academicians, students, researchers, scientists, and industry professionals around the world in the biomedical, health, and life science fields. Key features: Presents recent advances in neuropharmacology, covering the drugs that act on the central and peripheral nervous systems; Provides extensive explanations of various emerging research in this field; Explores the intricacy of neurological disorders Looks at existing and forthcoming therapeutic drug strategies"--
OCLC-licensed vendor bibliographic record.
Keywords: Neuropharmacology